Foreign bond markets and financial market development: International perspectives - Jonathan A. Batten; Warren P. Hogan; Peter G. Szilagyi (Asian Development Bank Institute (ADBI), 2009)
The domestic bond markets of the Asia and Pacific region have grown considerably since the Asian financial crisis of 1997, although they remain undeveloped relative to the region's weight in the world economy. This paper proposes that in order to encourage further development of these markets, regulators should make them more accessible to foreign borrowers. To that end we offer insights into the nature and mechanics of foreign bond issuance by investigating the key characteristics of 3,132 foreign bonds issued in 14 countries (other than the United States) between July 1928 and June 2009. We found that the foreign borrowers that tap domestic markets are overwhelmingly of high credit quality and comprise sovereigns, supranationals, and major financial institutions. There is a preference for simple fixed-rate payment structures, which can then be swapped into the currency and coupon type of choice using currency and interest rate derivatives. On the whole, the long-term viability of foreign bond markets appears linked to the presence of highly liquid foreign exchange and derivatives markets that facilitate risk management and transformation, enabling regulation that facilitates cooperation with market participants, the presence of benchmark issues, and competitive pricing between alternate market segments.
Keywords: F34; G18; O57; 330